2022
DOI: 10.1038/s41467-022-28340-6
|View full text |Cite
|
Sign up to set email alerts
|

Receptor-interacting protein kinase 2 (RIPK2) stabilizes c-Myc and is a therapeutic target in prostate cancer metastasis

Abstract: Despite progress in prostate cancer (PC) therapeutics, distant metastasis remains a major cause of morbidity and mortality from PC. Thus, there is growing recognition that preventing or delaying PC metastasis holds great potential for substantially improving patient outcomes. Here we show receptor-interacting protein kinase 2 (RIPK2) is a clinically actionable target for inhibiting PC metastasis. RIPK2 is amplified/gained in ~65% of lethal metastatic castration-resistant PC. Its overexpression is associated wi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 79 publications
1
13
0
Order By: Relevance
“…Inhibition of RIPK2 can prevent the production of tumorigenic IL-17 in colorectal cancer (Garo et al 2021 ). Recent study showed that RIPK2 reduced prostate cancer metastasis through regulating c-Myc stability and activity (Yan et al 2022 ). Our study supplemented understanding on the role of RIPK2 in PC, indicating that the expression of RIPK2 was aberrantly increased in PC and a higher expression of RIPK2 predicted a poorer prognosis of PC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of RIPK2 can prevent the production of tumorigenic IL-17 in colorectal cancer (Garo et al 2021 ). Recent study showed that RIPK2 reduced prostate cancer metastasis through regulating c-Myc stability and activity (Yan et al 2022 ). Our study supplemented understanding on the role of RIPK2 in PC, indicating that the expression of RIPK2 was aberrantly increased in PC and a higher expression of RIPK2 predicted a poorer prognosis of PC patients.…”
Section: Discussionmentioning
confidence: 99%
“…As illustrated by these three models, there is a large overlap in the Myc, AR, PI3K, and Erk 1/2 signaling pathways—all of which are major oncogenic conduits leading to cell growth and proliferation. Furthermore, in the recent RIPK2 model, receptor-interacting protein kinase 2 (RIPK2) has been found to strongly regulate the stability and activity of c-Myc [ 109 ]. This is done through the association of RIPK2 with a form of MEK (MAPKK) called MAPKK7 [ 109 ].…”
Section: Mouse Models Based On Signaling Pathwaysmentioning
confidence: 99%
“…Furthermore, in the recent RIPK2 model, receptor-interacting protein kinase 2 (RIPK2) has been found to strongly regulate the stability and activity of c-Myc [ 109 ]. This is done through the association of RIPK2 with a form of MEK (MAPKK) called MAPKK7 [ 109 ]. Invasive adenocarcinoma with metastasis to bone is observed in this model.…”
Section: Mouse Models Based On Signaling Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…The MYCN model and Braf V600E model are also accompanied by loss of Pten function. Furthermore, in the RIPK2 model, receptor-interacting protein kinase 2 (RIPK2) has been found to stabilize c-Myc, and is proposed as a therapeutic target in PCa metastasis [97]. As illustrated by these three models, there is a large overlap in the Myc, AR, and PI3K signaling pathways -all of which are major oncogenic conduits leading to cell growth and proliferation.…”
Section: Myc Pathwaymentioning
confidence: 99%